Obtain the general solution of the following differential equations.
1. ππ¦ + π¦πxππ₯ = πxππ₯
2. π₯ππ¦ = (πx β 2π¦)ππ₯
Obtain the particular solution satisfying the indicated conditions.
3. (2π¦ β π₯3)ππ₯ = π₯ππ¦, π¦(2) = 4
1.
"\\dfrac{dy}{1-y}=e^xdx"
Integrate
"-\\ln|1-y|=e^x-\\ln C"
"1-y=Ce^{-e^x}"
"y=1-Ce^{-e^x}"
2.
"y'+2\\dfrac{y}{x}=\\dfrac{e^x}{x}"
Integrating factor
"x^2y'+2xy=xe^x"
"d(x^2y)=xe^xdx"
Integrate
"\\int xe^xdx"
"\\int udv=uv-\\int vdu"
"u=x, du=dx"
"dv=e^xdx, v=\\int e^x dx=e^x"
"\\int xe^xdx=xe^x-\\int e^xdx=xe^x-e^x+C"
Then
"y=\\dfrac{e^x}{x}-\\dfrac{e^x}{x^2}+\\dfrac{C}{x^2}"
3.
Integrating factor
"\\dfrac{1}{x^2}y'-\\dfrac{2}{x^3}y=-1"
"d(\\dfrac{y}{x^2})=-dx"
Integrate
"\\dfrac{y}{x^2}=-x+C"
"y=-x^3+Cx^2"
"\ud835\udc66(2) = 4"
The particular solution satisfying the indicated conditions is
"y=-x^3+3x^2"
Comments
Leave a comment